Characterisation of the HIV inhibitory activity of vaginal lactobacilli isolates from young South African women at high risk of HIV acquisition - Manhanzva, Monalisa Tatenda (Division of Medical Virology, 2021)
Bacterial vaginosis (BV) is an important predisposing factor for the acquisition of human immunodeficiency virus (HIV) and other sexually transmitted infections (STIs) in South African women. However, the microbial causes and the immunomodulatory effects of BV are not yet fully understood, and effective treatment strategies do not exist. BV is associated with upregulated inflammatory cytokine levels in the female genital tract (FGT), which in turn may increase HIV infection risk by recruiting and activating HIV target cells, reducing epithelial barrier function and directly promoting HIV replication. Lactobacillus species on the other hand are thought to protect against HIV by competitive exclusion, producing virucidal hydrogen peroxide (H2O2), maintaining an acidic pH by producing lactic acid and regulating immune responses in the FGT. This dissertation aimed to characterise the relative HIV inhibitory properties of clinical Lactobacillus isolates, to evaluate the immunoregulatory properties of lactobacilli, and determine the mechanisms underlying these relationships. Vaginal Lactobacillus isolates (n=103), including L. crispatus, L. jensenii, L. johnsonii, L. mucosae, L. plantarum, L. ruminis, L. salivarius and L. vaginalis, were isolated from young South African women who participated in the Women's Initiative in Sexual Health (WISH) study. The production of pro-inflammatory cytokines (IL-6, IL-1α, IL-1β), chemokines (IL-8, IP-10, MIP-3α, MIP-1α, MIP-1β) and regulatory IL-1RA by vaginal epithelial cells in response to lactobacilli in the presence or absence of Gardnerella vaginalis ATCC 14018 and Prevotella bivia ATCC 29303, was measured using Luminex. Growth rates, bacterial sizes, adhesion to cervical (Ca Ski) and vaginal epithelial cells (VK2), culture pH changes and D/L-lactate production by the lactobacilli were also measured in vitro. The properties of vaginal Lactobacillus isolates were also compared to those of commercial probiotics and ATCC reference strains. In order to evaluate differences between lactobacilli isolates that induced low (termed “non-inflammatory”) versus high (termed “inflammatory”) levels of inflammatory cytokine production, the proteomic profiles of 22 inflammatory and 22 non-inflammatory Lactobacillus isolates were analysed using liquid chromatography tandem mass spectrometry (LC-MS/MS) to investigate the underlying mechanisms leading to the different inflammatory profiles. Lastly, the influence of Lactobacillus culture supernatants (n=16) on HIV infectivity was evaluated using a Luciferase Reporter Gene Assay in TZM-BL cells. Lactobacilli isolated from women with non-optimal microbiota produced less lactic acid and induced greater inflammatory cytokine production than those from women with optimal microbiota, with IL-6, IL-8, IL-1a, IL-1b, MIP-1a and MIP-1b production significantly elevated. Proteomics analysis showed that 164 proteins were differentially abundant between inflammatory lactobacilli and non-inflammatory lactobacilli. Functional analysis revealed that isolates inducing low levels of inflammatory cytokine production had a significantly higher relative abundance of membrane-associated cellular components, metabolic biological processes and enzymatic molecular functions compared to isolates that induced higher levels of inflammation. A subset of sixteen lactobacilli significantly suppressed IL-6 (adjusted p<0.001) and IL-8 (adjusted p=0.0170) responses to G. vaginalis while L. crispatus isolates suppressed inflammatory cytokines responses to P. bivia. Culture supernatants from the same 16 isolates significantly suppressed HIV infectivity in TZM-BL cells (p=0.0078). Lactobacilli adhesion to VK2 cells correlated negatively with IL-6, IL-8, MIP-1a and IL-1RA production. Lactobacillus beneficial characteristics were highly strainspecific and vaginal isolates out-performed commercial probiotics and ATCC strains. Lactobacillus growth rates, bacterial sizes and adhesion to VK2 cells did not differ significantly between isolates from women with non-optimal microbiota versus those from women with optimal microbiota. These findings show that, while cervicovaginal lactobacilli suppressed overall inflammatory responses to G. vaginalis and P. bivia, isolates from women with non-optimal microbiota were more inflammatory, had lower relative protein abundance and produced less antimicrobial lactic acid than isolates from women with optimal microbiota. Additionally, vaginal Lactobacillus isolates performed better than existing commercial probiotics, suggesting room for improvement of current probiotic formulations available on the South African market to improve BV treatment outcomes and reduce inflammation in the FGT.